The Prognostic Value of the Serum Levels of Brain Natriuretic Peptide, Troponin I, and D-Dimer, in Addition to the Neutrophil-to-Lymphocyte Ratio, for the Disease Evaluation of Patients with Acute Pulmonary Embolism - Bi W; Liang S; He Z; Jin Y; Lang Z; Liu H; Wang Y; Li S (International Journal of General Medicine, 2021)
Wenmiao Bi,1,* Shaoqing Liang,2,* Zhihong He,2 Ying Jin,2 Zhe Lang,2 Hongjuan Liu,2 Yi Wang,2 Shuhong Li2 1Department of Respiratory Medicine, Shijiazhuang People’s Hospital, Shijiazhuang, Hebei 050031, People’s Republic of China; 2Department of Emergency Medicine, Shijiazhuang People’s Hospital, Shijiazhuang, Hebei 050031, People’s Republic of China*These authors contributed equally to this workCorrespondence: Zhihong He; Ying JinDepartment of Emergency Medicine, Shijiazhuang People’s Hospital, 365 Jianhuanan Street, Yuhua District, Shijiazhuang City, Hebei 050031, People’s Republic of ChinaTel/Fax +86 311-69089120Email hezhihong_hzh83@21cn.com; jinying_shk23@21cn.comObjective: The present study aims to investigate whether the serum levels of brain natriuretic peptide (BNP), troponin I (TnI), and D-dimer, in addition to the neutrophil-to-lymphocyte ratio (NLR), can be used to determine the prognosis of patients with acute pulmonary embolism (APE).Methods: Data were collected from 72 patients that were diagnosed with APE in our hospital from January 2015 to December 2018. These patients were divided into three groups: a high-risk group (n = 10), a moderate-risk group (n = 33), and a low-risk group (n = 29). The serum levels of BNP, TnI, and D-dimer were determined, and the NLR was measured. The receiver operating characteristic (ROC) curve was used to analyze the diagnostic value of the single and combined detection of BNP, TnI, and D-dimer, and the NLR was used to determine the prognosis of patients with APE.Results: The serum levels of BNP, TnI, and D-dimer were significantly higher in the high-risk group than they were in the moderate-risk and low-risk groups (P < 0.05). The serum levels of BNP, TnI, and D-dimer were also significantly higher in the moderate-risk group than they were in the low-risk group (P < 0.05). The serum levels of BNP, TnI, and D-dimer, as well as the NLR, were all significantly higher in the death group than they were in the survival group (P < 0.05). For the combined detection of the four indices, the area under the ROC curve was 0.92, the sensitivity was 0.889, and the specificity was 0.904; each of these values was higher than the corresponding values of single detection.Conclusion: In patients with APE, higher serum levels of BNP, TnI, D-dimer and NLR are associated with a higher risk stratification, greater severity of disease, and an increased risk of death.Keywords: brain natriuretic peptide, troponin I, D-dimer, neutrophil-to-lymphocyte ratio, pulmonary thromboembolism, acute pulmonary embolism